Regulation of Krüppel homolog 1 expression by photoperiod in the bean bug, Riptortus pedestris. (15th December 2020) - Dong, Li; Udaka, Hiroko; Numata, Hideharu; Ito, Chihiro
Abstract: In Riptortus pedestris (Hemiptera, Alydidae), adult females develop their ovaries under long‐day conditions (LD), but enter reproductive diapause with suppression of ovarian development under short‐day conditions (SD). This photoperiodic response is regulated by juvenile hormone (JH). Krüppel homolog 1 ( Kr‐h1 ) encodes a JH‐inducible transcriptional factor and plays a pivotal role for reproduction in some insects. In the present study, we molecularly characterized Kr‐h1 and investigated Kr‐h1 expression patterns under SD and LD in R . pedestris . The open reading frame of Kr‐h1 was 1320 bp encoding a protein of 440 amino acids. The deduced protein contained eight conserved C2 H2 ‐type zinc finger domains. The expression levels of Kr‐h1 increased from 5 days and peaked at 7 days after transfer from SD to LD. By contrast, Kr‐h1 was constantly expressed at a low level under SD. Topical application of a JH analogue induced ovarian development and Kr‐h1 expression even under SD, suggesting that Kr‐h1 is a JH‐inducible gene in R . pedestris . Then, we examined the effect of knockdown of circadian clock genes Clock ( Clk ) and mammalian‐type cryptochrome ( cry‐m ) by RNA interference (RNAi) on the ovarian development and Kr‐h1 expression. Clk RNAi prevented ovarian development and decreased the Kr‐h1 expression under LD, whereas cry‐m RNAi induced ovarian development and Kr‐h1 expression under SD. These results imply that JH secretion is prevented by Clk RNAi under LD and induced by cry ‐ m RNAi under SD. From these results, we suggest that Kr‐h1 expression is JH dependent and closely correlates with photoperiodic regulation of ovarian development. Abstract : Application of juvenile hormone analogue increased expression of Krüppel homolog 1 ( Kr‐h1 ) in Riptortus pedestris . Kr‐h1 expression was low under diapause‐inducing short‐day conditions, whereas high under diapause‐averting long‐day conditions. RNAi of clock genes Clock and mammalian‐type cryptochrome disrupted the photoperiodic response in Kr‐h1 expression as well as in ovarian development.